2021
DOI: 10.1007/s11852-021-00826-3
|View full text |Cite
|
Sign up to set email alerts
|

Constructed floating wetlands made of natural materials as habitats in eutrophicated coastal lagoons in the Southern Baltic Sea

Abstract: Eutrophication remains an environmental challenge in lagoons along the Southern Baltic Sea. Floating islands planted with emergent macrophytes are an option to remove nutrients from eutrophicated waters. Furthermore, floating wetlands offer other ecosystem services such as the provision of habitats. Numerous scientific studies have been conducted; however most remain on the laboratory scale. This research explores the challenges associated with installations in coastal environments and focuses on sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Thus, it is of primary importance to study the FWs system in simulated coastal conditions to assess its durability and lifespan. This research challenge was also identified in the bibliometric analysis of Colares et al [37], and the research work of Karstens et al [38] who indicate that most studies about FWs remain on the laboratory-or pilot-scale, and point out the need to assess the behavior of the floating carrier in the natural environment.…”
Section: Economic Evaluationmentioning
confidence: 95%
“…Thus, it is of primary importance to study the FWs system in simulated coastal conditions to assess its durability and lifespan. This research challenge was also identified in the bibliometric analysis of Colares et al [37], and the research work of Karstens et al [38] who indicate that most studies about FWs remain on the laboratory-or pilot-scale, and point out the need to assess the behavior of the floating carrier in the natural environment.…”
Section: Economic Evaluationmentioning
confidence: 95%
“…The applied ecosystem service assessment is based on the Marine Ecosystem Services Assessment Tool (MESAT) [32]. In general, MESAT assesses changes in ES provision between different time periods [32], but it can also be used for different scenarios [33]. It is based on the Common International Classification of Ecosystem Service (CICES) and can be applied in a qualitative and semi-quantitative way.…”
Section: Ecosystem Service Assessmentsmentioning
confidence: 99%
“…In addition, floating islands attenuate wave energy and water flow and are consequently able to enhance particle settling and nutrient burial [38][39][40]. Floating wetlands with native emergent macrophytes were tested for the first time in Baltic lagoons in 2018 [39,40] and turned out to be a valuable refuge for aquatic fauna such as the endangered eel [33].…”
Section: Floating Artificial Wetlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many urban water bodies native vegetation, both riparian and submerged, are scarce to non-existent compared to less altered aquatic ecosystems. In these cases FTW vegetation may mimic natural wetlands and play multiple roles (O'Hare et al, 2018), providing a refuge for small fish and a forage ground for birds (Karstens et al, 2021), a food source for larval insect (e.g. lepidoptera) (Gross et al, 2001), and a complex physical environment on both the micro and macro-scale (Dibble et al, 2006).…”
Section: Introductionmentioning
confidence: 99%